Effects of exogenous hormones on the regeneration of juveniles from Sargassum fusiforme holdfasts - Luo, Lin; Zuo, Xiaojie; Guo, Lina; Pang, Guanfeng; Ma, Zengling; Wu, Mingjiang; Chen, Binbin (Frontiers in Marine Science, 2023)
During the cultivation of Sargassum fusiforme, sexual reproduction of superior strains can hinder the stable inheritance of their desirable traits and reduce their economic benefits. However, vegetative reproduction of S. fusiforme holdfasts has high potential for subculture. In this study, we investigated the effects of different concentrations of α-naphthaleneacetic acid (NAA), gibberellin (GA3), and 6-benzyladenine (BAP) on the growth and regeneration of S. fusiforme holdfasts. Exogenous application of 1.5, 2 mg·L-1NAA, 1.5 mg·L-1 GA3 or 2, 3 mg·L-1BAP significantly promoted photosynthetic activity and the absorption and utilization of nitrate nitrogen in S. fusiforme holdfasts, thus improving the relative growth rate (RGR) and regeneration rate (RR) and shortening the time for the regeneration of juveniles from S. fusiforme holdfasts to around the 6th day. Among these, the RGR and RR at the end of the culture period with 1.5 mg·L-1 of NAA increased by 118.9% and 67.4%, respectively, compared with those of the control group. However, treatment with 1.5 mg·L-1 GA3 increased the RR of S. fusiforme holdfasts by 58.8% compared with that of the control group. Under BAP treatment at 3 mg·L-1, the RR of S. fusiforme holdfasts increased by 23.4% compared with that of the control group; its promoting effect was thus weaker than that of NAA and GA3. When the concentration of GA3 or BAP was too high (3 mg·L-1; 5 mg·L-1), the RR of the holdfasts decreased by 46.5% and 42.8%, respectively compared with that of the control group. Therefore, exogenous application of NAA at 1.5 mg·L-1, GA3 at 1.5 mg·L-1, and BAP at 3 mg·L-1 can be used to induce regeneration of S. fusiforme holdfasts, shorten the culture time of regenerated seedlings, and obtain more regenerative seedlings, thereby improving economic efficiency.